18F-fluoro-deoxy-glucose positron emission tomography (18F-FDG-PET) for assessment of enteropathy-type T cell lymphoma. Issue 3 (1st March 2003) - Hoffmann, M; Vogelsang, H; Kletter, K; Zettinig, G; Chott, A; Raderer, M
Abstract : Background and aims: Enteropathy-type T cell lymphoma (ETCL) represents a relatively rare disease, accounting for less than 1% of non-Hodgkin's lymphomas. ETCL is an aggressive lymphoma which may either present de novo or arise in the context of longstanding or untreated coeliac disease (CD). The aim of this study was to evaluate the potential of 18F-fluoro-deoxy-glucose positron emission tomography (18F-FDG-PET) for imaging of ETCL. Furthermore, we wished to evaluate whether the presence of CD might provide a potential diagnostic obstacle to imaging of lymphoma due to unspecific 18F-FDG uptake and whether accumulation of 18F-FDG within the gut correlates with activity of CD. Patients and methods: We retrospectively analysed patients with ETCL and individuals suffering from CD undergoing 18F-FDG-imaging at our PET unit. Material for histological reassessment by a reference pathologist had to be available for inclusion of patients in the analysis. Whole body 18F-FDG-PET scans were performed 40 minutes following injection of 300–380 MBq of 18F-FDG. Images were reconstructed iteratively. In areas with focally elevated FDG uptake and in case of diffusely elevated intestinal 18F-FDG accumulation, standard uptake values (SUVs) were calculated. Results: During a period of two years, five patients (one male, four female) with a mean age of 56.4 years (range 44–62) with a diagnosis of ETCL underwent 18F-FDG-PET. Four of these patients were imaged before application of cytotoxic treatment while one patient had regular PET scans for follow up. All four patients undergoing pre-therapeutic imaging showed markedly elevated intestinal 18F-FDG uptake, with a maximal SUV of 6.4–8.0 (mean 7.15 (SD 0.82)). The patient imaged following surgery and cytotoxic therapy had no pathologic 18F-FDG uptake which was found to correlate with normal duodenal mucosa, as evidenced by repeated biopsies and conventional imaging methods. During the same time span, 12 patients (five male, seven female) with a mean age of 63.8 years (range 42–82) suffering from CD were imaged. Four of these patients showed no elevated intestinal 18F-FDG uptake while five had minor diffuse intestinal 18F-FDG accumulation with SUVs ranging between 2.2 and 4.6 (mean 3.4 (SD 0.89)). In the remaining three patients with diffuse intestinal 18F-FDG uptake, no SUV could be calculated. SUVs in patients with ETCL were remarkably higher than in patients suffering from CD (p=0.011), irrespective of the activity of CD at the time of imaging. Conclusion: In spite of the relatively small number of patients, our results clearly indicate the potential value of 18F-FDG-PET for diagnosing and imaging ETCL. In addition, the data also suggest that 18F-FDG-PET may lead to early diagnosis in individuals developing ETCL in the context of longstanding CD. This is due to the fact that 18F-FDG does not appear to significantly accumulate in the gut of patients with CD, irrespective of disease activity.